2022
DOI: 10.1177/10781552221081387
|View full text |Cite
|
Sign up to set email alerts
|

Oral cancer awareness and education within the pharmacy profession

Abstract: The incidence of oral cancers are rising in the UK, with early detection a significant positive prognostic factor. The Covid-19 pandemic has negatively impacted patients access to dental services, reducing a potential avenue to diagnosis. Community pharmacists are well positioned to play an expanded role in supporting earlier detection. This study seeks to identify levels of awareness and knowledge of oral cancer amongst community pharmacists, to inform development of educational resources. A cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…13 Patient education on oral cancer risk factors, oral cancer screening, oral cancer self-examination, and HPV vaccination are laudable strategies for oral cancer prevention and control. 14,15 These educational interventions can promote awareness and knowledge on oral cancer, and may bring about an expansion in the population who presents to primary care with precancerous or early form of the disease; hence reducing the rate of advance-stage clinical presentation of the disease. 16 Dentists in Nigeria-particularly those who are specialists in oral medicine, oral and maxillofacial surgery, and oral pathology-have a very crucial responsibility in the prevention, early diagnosis, and treatment of oral cancer, and sometimes may be the first clinician to diagnose such cases during routine examination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Patient education on oral cancer risk factors, oral cancer screening, oral cancer self-examination, and HPV vaccination are laudable strategies for oral cancer prevention and control. 14,15 These educational interventions can promote awareness and knowledge on oral cancer, and may bring about an expansion in the population who presents to primary care with precancerous or early form of the disease; hence reducing the rate of advance-stage clinical presentation of the disease. 16 Dentists in Nigeria-particularly those who are specialists in oral medicine, oral and maxillofacial surgery, and oral pathology-have a very crucial responsibility in the prevention, early diagnosis, and treatment of oral cancer, and sometimes may be the first clinician to diagnose such cases during routine examination.…”
Section: Introductionmentioning
confidence: 99%
“…Patient education on oral cancer risk factors, oral cancer screening, oral cancer self‐examination, and HPV vaccination are laudable strategies for oral cancer prevention and control. 14 , 15 These educational interventions can promote awareness and knowledge on oral cancer, and may bring about an expansion in the population who presents to primary care with precancerous or early form of the disease; hence reducing the rate of advance‐stage clinical presentation of the disease. 16 …”
Section: Introductionmentioning
confidence: 99%
“…This study demonstrates a need for profession development aimed at community pharmacists who can aid in improving rates of early detection of oral cancers. 12 In Palestine, a recent study was conducted by Shadid et al at the Arab American University of Jenin which evaluated the level of oral cancer knowledge of undergraduate students in their 4 th and 5 th year at dental school as well as intern dentists. The authors reported that the majority of respondents had poor knowledge about clinical features, risk factors, and early detection of oral cancers.…”
Section: Introductionmentioning
confidence: 99%